Re-examination of the effect of ownership structure on financial reporting: Evidence from share pledges in China - Zhizhong Huang; Qingmei Xue (China Journal of Accounting Research, 2016)
In this paper, we present evidence that firms with concentrated ownership manage earnings when their large shareholders have an incentive to do so. The large shareholders of Chinese public firms often pledge their shares for loans. Before the split share reform in 2006, loan terms were based on the book value of the firm. Since then, the share price has become critical for share pledged loans. We postulate that the reform triggered large shareholders' incentive to influence financial reports. Using a sample of non-state-owned enterprises, we test the effect of share pledges on earnings smoothing and how this effect changes after the reform. Our results suggest that share pledging firms smooth their earnings more than other firms, but these results are only found after the split share reform. Accordingly, our results provide more direct evidence on the effect of ownership concentration on financial reporting.
Keywords: 650; Ownership concentration; Share pledges; Earnings smoothing; Split share reform